2014
DOI: 10.1108/imds-10-2013-0455
|View full text |Cite
|
Sign up to set email alerts
|

The mission statement: organisational culture perspective

Abstract: Purpose – The purpose of this paper is to contribute to the understanding of mission statement contents and its function in guiding employee's behaviour from the organisational culture (OC) perspective. Design/methodology/approach – The research is based on a mixed method approach. The quantitative content analysis of mission statements was performed on a sample of 222 Slovenian companies. Mission statement's keywords were analysed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 26 publications
2
46
0
1
Order By: Relevance
“…This fact is one of the main critical findings of our study and is also consistent with the literature. For instance, in a recent study by Babnik et al [25] on mission statements' content dimensions among Slovenian organizations, similar orientations were revealed in line with the current study such as orientation towards stability, development and growth. Likewise, Sidhu examined the relationship between mission statement comprehensiveness and performance via regression analysis and found a significant positive effect of the former on the latter [26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This fact is one of the main critical findings of our study and is also consistent with the literature. For instance, in a recent study by Babnik et al [25] on mission statements' content dimensions among Slovenian organizations, similar orientations were revealed in line with the current study such as orientation towards stability, development and growth. Likewise, Sidhu examined the relationship between mission statement comprehensiveness and performance via regression analysis and found a significant positive effect of the former on the latter [26].…”
Section: Discussionsupporting
confidence: 91%
“…Manufacturing coke, refined petroleum products and nuclear fuel 24 Manufacturing chemicals and chemical products 25 Manufacturing rubber and plastic products 26…”
Section: Discussionmentioning
confidence: 99%
“…The people who perceive the organization mission and thereby shape the culture in an organization, generating values and customary daily life at work, tend to be committed to their organization (2005, p.72). Babnik et al (2014) share the same view. Therefore, there can be an assumption that a mission adds particular value to a strong organizational culture, while increasing personnel motivation.…”
Section: Literature Reviewmentioning
confidence: 84%
“…For instances, Williams et al (2014) suggested the use of top management commitment as a moderator in a new model and David et al (2014) recommended a reexamination of the mission statement from a customer perspective to align the firm's marketing strategy as a new direction in mission statement studies. These two approaches locate their solution within the strategic school of thought (Babnik, Breznik, Dermol, & Trunk Širca, 2014;Campbell, Nash, Devine, & Young, 1992). Scholars in the strategic school of thought focus on the strategic arrangement (for examples: policies, procedures, processes, systems and goals) of the organisation conditions to study mission statement effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…This strategic school is differentiated from the cultural school of thought which view the mission statement as a text document that shapes the values, identity, meaning, and culture of the organisation (Campbell et al, 1992;Desmidt & Heene, 2003;Ledoux, 2005;Swales & Rogers, 1995). The primary emphasis of the cultural school of thought is not to determine mission statement effective per se, but rather to study how the mission statement shapes and provides meaning (Babnik et al, 2014). Our study extended Campbell's (1991) mission model by investigating the effect of the fit perspective of the organisation's strategic and cultural elements between organisation's mission statement and the performance outcomes.…”
Section: Introductionmentioning
confidence: 99%